Detection of Chemical Warfare Agents and Biological Warfare Agents - Fakron, Malik M.A. (Chemical Warfare and Environmental Warfare Operations, Edition 1, 2025)
Detection in chemical warfare and biological warfare has great benefits for warfare management. There are several types of detectors for chemical warfare agents and biological warfare agents. The major task of this paper is to review chemical warfare agents, biological warfare agents, and the techniques of detection technology for chemical warfare agents and biological warfare agents. The paper also discusses the use of various sensors to detect chemical and biological warfare agents, providing effective early warning information. The application of detection has proven very effective in reducing the hazardous effects of chemical and biological agents in war. This provides an early warning tool for the chemical and biological materials used in warfare, reduces the cost of warfare, and also reduces environmental problems due to the excessive use of chemical and biological agents.